(untitled) (SCIENCE TIME JOURNAL, 2026)
The modern diet is saturated with sugar-sweetened beverages, which are primary drivers of metabolic disorders and obesity. This study provides a comparative analysis of sugar concentrations in popular drinks using the refractometric method. The results revealed that "healthy" alternatives, such as strawberry yogurt (12.5% Brix) and freshly squeezed apple juice (11.7% Brix), contain significantly higher sugar levels than carbonated drinks like Coca-Cola (8.5% Brix). While natural juices provide essential vitamins and minerals, commercial dairy and instant products often harbor "hidden" added sugars that complicate dietary tracking. The findings highlight the necessity of distinguishing between natural and added sugars for better nutritional management.